A special characteristic of an earthquake response spectrum detected in Turkey - Mohammad Zaher Serdar (17191381) (2022)
This article highlights a special characteristic of response spectrum behavior associated with a devastating earthquake recorded in Turkey. The behavior poses a threat to long-period structures (mid-to high-rise buildings and special structures). For this paper, a group of seven accelerations records was used from different parts of the world to validate the analysis tools for the accelerations record of interest. In addition, records of the special event from two different stations were used to eliminate the possibility of malfunctioning of the recording device. These records were converted into response spectrums as the form usually used in earthquake engineering. Response spectrums resulting from this event had two high response areas: 1) one in the short domain of periods (as generally known in typical response spectrum plots) 2) another one that is effecting long domain periods (which typically does not cause high response from earthquakes due to low value of response spectrum typically plotted in this domain). This paper is expected to raise awareness of the importance of locally developed response spectrums to cope with the possibilities of irregular and uncaptured events in international codes. Furthermore, it aims to promote the analysis using time-history accelerations records of structures from local records as a better tool to interpret the expected behavior of the structures. Other Information Published in: Materials Today: Proceedings License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matpr.2022.04.407